A novel SARS-CoV-2 subunit vaccine engineered on an immune-activating platform technology - Edward J. Quinlan; Richard Chubet; Peter Leonardi (Taylor & Francis Group, 2022)
While there are several SARS-CoV-2 vaccines currently available, additional options must be provided that are safe, effective, and affordable for the entire global population. We have developed a novel immune activating platform technology that will fill this need. This recombinant platform protein is produced in insect cells using baculoviral expression technology similar to what is currently used for several other approved vaccines as well as employed by myriad GMP facilities globally. Thus, infrastructure exists for rapid scale up following initial optimizations. Here we report initial results for a SARS-CoV-2 vaccine (OMN008) based on our platform technology. Unadjuvanted OMN008 vaccination resulted in robust antigenicity and neutralization. Additionally, OMN008 vaccination induced a specific CD8 T-cell response. All of these results taken together indicate OMN008 may be an excellent candidate to fill gaps left by the currently available vaccines. Further testing is necessary to fully optimize production; however, overall cost of production should remain low given the simple formulation of this recombinant platform.